Análise técnica e econômica para geração distribuída a partir do biogás em pequenas propriedades agropecuárias - Tomasi, Rodrigo (2019)
The pollutant potential of animal waste can be minimized with the use of anaerobic biodigesters, which deal with waste properly and generates biogas with potential to be used in several applications, including electric power generation. Distributed energy is a huge possibility for biogas applications and for development of rural areas, which provides a reduction on the environmental impact and strengthens the rural activity with a new product. However, the use of biodigesters and biogas conversion into electricity still has little adherence, since the great majority of farms are defined as family farming and investment cost is impracticable. In this scenario, this work presents a technical and economic analysis about biogas generator sets and the feasibility of distributed energy in small farms located in Santa Catarina State. A methodology is used to estimate the capacity of biogas production for a range from 100 to 1100 pigs in Growth and Termination Units. From this, three generator groups consisting of Otto cycle combustion engine and three-phase generators are defined, capable of generating 5.71, 6.70 and 11.10 kW of electric power. From the mass and energy balances and the methane concentration into biogas, the amount of daily operating hours of the generator set and the monthly operational cost are estimated. The economic analysis is performed by the Net Present Value (NPV), considering that the investment is financed in 5 years with interest of 4.6% p.a. VPL values were reached for the whole range of animals, which for 1100 pigs it is in the order of R$ -26,000.00, R$ -19,000.00 and R$ -9,000.00 for the three groups, result which can be improved to R$ 8,000.00, R$ 15,000.00 and R$ 24,000.00 in case if there is a significant reduction in operating costs and increasing efficiency of the generator set.